2024
DOI: 10.1039/d3cc05379b
|View full text |Cite
|
Sign up to set email alerts
|

Continuous selective conversion of methane to methanol over a Cu-KFI zeolite catalyst using a water–O2 mixture as the oxygen source

Hailong Zhang,
Jiaxiu Guo,
Yi Cao

Abstract: The article highlights the potential of Cu-KFI zeolites as catalysts in the continuous conversion of methane to methanol using water and O2 as the oxidants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In copper zeolite methane oxidation literature, it has been proposed that water can oxidize Cu(I) to Cu(II) and ultimately recycle CH 4 reduced active sites ,, with some taking issue that the reaction is endergonic at 473 K. , Upon exposure of CH 4 reduced Cu-MOR to water at 200 °C, we do not observe copper oxidation by XAS (Figure A). In continuous methane oxidation systems, it has been suggested that water can be used to oxidize mononuclear and binuclear Cu(I) sites. Here, we do not observe water oxidizing either the mononuclear Cu(I) or the bicuprous sites, suggesting that water’s role as an oxidant in continuous systems should be reconsidered. Given the small amount of oxygen needed to have an effect in our stepwise system (as suggested by Brezicki et al), oxygen leaks could be playing a role in the continuous system as well.…”
mentioning
confidence: 62%
“…In copper zeolite methane oxidation literature, it has been proposed that water can oxidize Cu(I) to Cu(II) and ultimately recycle CH 4 reduced active sites ,, with some taking issue that the reaction is endergonic at 473 K. , Upon exposure of CH 4 reduced Cu-MOR to water at 200 °C, we do not observe copper oxidation by XAS (Figure A). In continuous methane oxidation systems, it has been suggested that water can be used to oxidize mononuclear and binuclear Cu(I) sites. Here, we do not observe water oxidizing either the mononuclear Cu(I) or the bicuprous sites, suggesting that water’s role as an oxidant in continuous systems should be reconsidered. Given the small amount of oxygen needed to have an effect in our stepwise system (as suggested by Brezicki et al), oxygen leaks could be playing a role in the continuous system as well.…”
mentioning
confidence: 62%